Genome-wide investigation of mRNA lifetime determinants in Escherichia coli cells cultured at different growth rates - Esquerré, Thomas (BMC Genomics, 2015)
BACKGROUND: Changes to mRNA lifetime adjust mRNA concentration, facilitating the adaptation of growth rate to changes in growth conditions. However, the mechanisms regulating mRNA lifetime are poorly understood at the genome-wide scale and have not been investigated in bacteria growing at different rates. RESULTS: We used linear covariance models and the best model selected according to the Akaike information criterion to identify and rank intrinsic and extrinsic general transcript parameters correlated with mRNA lifetime, using mRNA half-life datasets for E. coli, obtained at four growth rates. The principal parameter correlated with mRNA stability was mRNA concentration, the mRNAs most concentrated in the cells being the least stable. However, sequence-related features (codon adaptation index (CAI), ORF length, GC content, polycistronic mRNA), gene function and essentiality also affected mRNA lifetime at all growth rates. We also identified sequence motifs within the 5′UTRs potentially related to mRNA stability. Growth rate-dependent effects were confined to particular functional categories (e.g. carbohydrate and nucleotide metabolism). Finally, mRNA stability was less strongly correlated with the amount of protein produced than mRNA concentration and CAI. CONCLUSIONS: This study provides the most complete genome-wide analysis to date of the general factors correlated with mRNA lifetime in E. coli. We have generalized for the entire population of transcripts or excluded determinants previously defined as regulators of stability for some particular mRNAs and identified new, unexpected general indicators. These results will pave the way for discussions of the underlying mechanisms and their interaction with the growth physiology of bacteria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1482-8) contains supplementary material, which is available to authorized users.